Pelatihan Pembuatan Pupuk Organik Berbasis Limbah Kulit Kopi Desa Curahpoh - Setiyono; Arum, Ayu Puspita; Meliala, Susan Barbara Patricia Sembiring; Savitri, Dyah Ayu; Nisak, Fauziatun; Ayuningtyas, Putri Larasati; Sari, Andini Permata (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Coffee as one of the plantation commodities has an important role in the growth of the Indonesian economy. One of the areas producing Robusta and Arabica coffee located at the foot of Mount Argopuro, Curahdami District, Bondowoso Regency, East Java Province is Curahpoh Village. Farmers of Curahpoh Village who are members of the LMDH Argo Santoso Farmer Group actively cultivate coffee, especially Robusta coffee, as a source of livelihood for the community. The Robusta coffee processing process will produce waste in the form of coffee skins which can cause unpleasant odors and pollute the environment. The community service activities of this Fostered Village began with the Argo Santoso Forest Village Community Institution (LMDH) farmer group, Curahpoh Village, Bondowoso Regency, East Java Province. This program aims to train the Curahpoh Village community to process coffee skin waste into organic fertilizer. This community service activity was attended by 20 people. This program was implemented through the stages of socialization, practice and evaluation. The results of the program showed that participants were able to master the technique of processing organic fertilizer from coffee skin waste well.